Pressure dependence of the solubility of light fullerenes in n-nonane. (September 2017) - Semenov, Konstantin N.; Charykov, Nikolay A.; López, Enriqueta R.; Fernández, Josefa; Sharoyko, Vladimir V.; Murin, Igor V.
Highlights: C60 and C70 fullerenes SLE in n-nonane up to 100 MPa at (298.3–353.3) K was studied. Thermodynamic calculations under isobaric and isothermal conditions were performed. Solubility of C60 and C70 in nonane increases monotonously with pressure. The temperature dependence of the solubility of C60 in n -nonane is non-monotonic. Solubility of C70 in nonane shape is due to crystallization of non-solvated C70 . Abstract: Solubility of light fullerenes (C60 and C70 ) in n -nonane was investigated in the ranges of pressure form 0.1 MPa up to 100 MPa and temperature from 298.3 K to 353.3 K. Under isothermal conditions, the solubility, expressed as weight fraction of the fullerene in the solution, increases monotonously with increasing pressure. At ambient pressure, we have found that the temperature dependence of the solubility of C60 in n -nonane is non-monotonic: the solubility diagram consists of two branches corresponding to crystallization of different solid phases and one invariant point corresponding to simultaneous saturation of both phases. At 0.1 MPa, the solubility diagram of the binary system C70 – n -nonane in the analysed temperature range consists of only one branch corresponding to crystallization of non-solvated C70 .